2009
DOI: 10.1186/1746-1448-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of poly-extremophilic Bacteria: Does combining the extremes of high salt, alkaline pH and elevated temperature approach a physico-chemical boundary for life?

Abstract: Bacterial microorganisms that grow optimally at Na+ concentrations of 1.7 M, or the equivalent of 10% (w/v) NaCl, and greater are considered to be extreme halophiles. This review focuses on the correlation between the extent of alkaline pH and elevated temperature optima and the extent of salt tolerance of extremely halophilic eubacteria; the focus is on those with alkaline pH optima, above 8.5, and elevated temperature optima, above 50°C. If all three conditions are required for optimal growth, these microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 39 publications
5
69
0
Order By: Relevance
“…Such interactions between stress parameters are frequently likely to be multifactorial. Indeed, since no microbial isolates to date have been found to exhibit cell division under a combination of extremely high salinity, temperature (Ͼ60°C), and pH (Ͼ8), these conditions may be collectively prohibitive to life (8,16). Other combinations of stress parameters may also determine the limits for cell division within extreme environments.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such interactions between stress parameters are frequently likely to be multifactorial. Indeed, since no microbial isolates to date have been found to exhibit cell division under a combination of extremely high salinity, temperature (Ͼ60°C), and pH (Ͼ8), these conditions may be collectively prohibitive to life (8,16). Other combinations of stress parameters may also determine the limits for cell division within extreme environments.…”
mentioning
confidence: 99%
“…Despite our knowledge of the physicochemical boundaries for microbial cell division having been greatly advanced over the past three decades, we are only beginning to understand how interactions between different stressors define biological permissiveness for natural ecosystems (8,(13)(14)(15)(16)(17)(18). In particular, while several studies have identified minimal and maximal limits for microbial life in response to the surrounding environment (1,5,(19)(20)(21), there is a paucity of information on how rates of cell division are impacted by multiple stress parameters within extreme habitats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The halophilic alkalithermophiles are a unique group of polyextremophiles that grow optimally under the combined conditions of extreme salinity, alkaline pH, and elevated temperature. The isolation and description of these recently discovered polyextremophiles have extended the known physical and chemical boundaries for life and have provided excellent models for the study and characterization of novel physiologies and biochemical pathways (2,3).…”
mentioning
confidence: 99%
“…Additionally to research into the in situ activities of microbial communities under extreme conditions [6 -8], the isolation and physiological characterization of microbial strains has been essential to our knowledge of the physico-chemical limits for life, as it has enabled us to investigate the growth phenotypes of extremophilic taxa in detail. Based on cardinal growth data (minimal, optimal and maximal conditions for cell division), several efforts to characterize the global-scale boundary space for bacterial and archaeal cell division have now been made, using two-and three-dimensional maps of habitability [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%